Education and HIV/AIDS - Biggs, Nalini Asha (Education as a humanitarian response., 2012)
"Education and HIV/AIDS draws together contributors with expertise in HIV/AIDS and education working around the world, including Sub-Saharan Africa, Southeast Asia, Europe, the USA and the Caribbean, from a variety of perspectives. Contributors explore the changing nature of education in light of this epidemic, as well as the impact of public health issues on educational institutions, in a range of different contexts. Within each chapter, the contributors pull apart a variety of relationships HIV/AIDS has with education; some provide a comparative analysis of global responses and international politics, others use small case studies to explore how local culture and tradition impacts these issues. Each chapter contains a summary of the key points and issues within each chapter to enable easy navigation, key contemporary questions to encourage active engagement with the material and references to seminal texts and cutting-edge research to prompt further reading and discussion"--Provided by publisher.